2018
DOI: 10.1039/c8cp03842b
|View full text |Cite
|
Sign up to set email alerts
|

Defining the conditional basis of silicon phthalocyanine near-IR ligand exchange

Abstract: Bond cleavage reactions initiated by long-wavelength light are needed to extend the scope of the caged-uncaged paradigm into complex physiological settings. Axially unsymmetrical silicon phthalocyanines (SiPcs) undergo efficient release of phenol ligands in a reaction contingent on three factors - near-IR light (690 nm), hypoxia, and a thiol reductant. These studies detail efforts to define the mechanistic basis for this unique conditionally-dependent bond cleavage reaction. Spectroscopic studies provide evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…The mediation of Si−O dissociation with a water molecule was also suggested by Anderson et al . for a SiPc compound with alkoxy and phenoxy ligands, further supporting the current evidence that Si−O dissociation occurs through NIR irradiation‐supported hydrolysis.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The mediation of Si−O dissociation with a water molecule was also suggested by Anderson et al . for a SiPc compound with alkoxy and phenoxy ligands, further supporting the current evidence that Si−O dissociation occurs through NIR irradiation‐supported hydrolysis.…”
Section: Methodssupporting
confidence: 82%
“…, respectively), while exhibiting very high Gibbs activation energies (209.0 and 161.8 kJ ⋅ mol −1 , respectively), which are too high to proceed at room temperature. Note that the reported activation energies of concerted ligand substitution reactions of SiPc with phenoxy ligand are 147.3 and 121.3 kJ ⋅ mol −1 for neutral and radical anion species, respectively, which are much lower than those of 2 and 2 −. , thus indicating that the concerted reaction of path (C) barely proceeds.…”
Section: Methodsmentioning
confidence: 91%
“…Additionally, if the antibody conjugate was bound to its cognate antigen, similar changes were observed (Figure g). Following this reaction, NIR-fluorescence was lost, and IR700 could not reach the triplet state; therefore, we hypothesize that no further photochemical reaction is possible at this point.…”
Section: Discussionmentioning
confidence: 96%
“…DFT calculations indicated that the attack of water as a nucleophile on the radical-anion center is more feasible than an attack on the neutral complex. 958 …”
Section: Photorelease From Coordination Compoundsmentioning
confidence: 99%